Risk of developing Temporomandibular Disorder in patients who suffered condyle fracture: A literature review (Research, Society and Development, 2023)
Objectives: To review the current literature on the risks of patients who have suffered a condylar fracture developing temporomandibular disorders, noting its influence on the time factor, treatment and reiterate the importance of dentistry in the process of monitoring condylar fractures for a better quality of life for patients affected. Methodology: The present study was developed through a bibliographic review, in which we sought to collect data from published studies involving the risk of developing temporomandibular disorders in patients who suffered condylar fractures. The search was carried out in the Scielo and Pubmed databases, academic search sites, and reference books on the subject. Results: Reported by the authors, these fractures, due to their anatomy and proximity to the temporomandibular joint, demand a properly trained professional, who performs a thorough anamnesis and ensures an individualized treatment plan. Regardless of the treatment chosen, to secure a good prognosis, follow-up at all stages must be carried out together. Conclusion: It was observed that the association of patients who suffered a condylar fracture with the appearance of temporomandibular disorders is of great relevance due to the high prevalence of their risks associated with these conditions to minimize punctual sequelae after the disease. Conservative treatment was found to be effective in promoting recovery and minimizing impacts on the patient's quality of life, but given other treatment modalities, the individual characteristics of each patient must be evaluated.